A powder spraying process for aluminum alloy frame for new energy vehicles

Through the pretreatment of the aluminum alloy frame and the spraying process using special powder coatings, the problem of insufficient corrosion resistance and easy cleaning in new energy vehicles is solved, and excellent corrosion resistance and easy cleaning performance is achieved.

CN117000564BActive Publication Date: 2025-04-29AN HUI KRANT ALUMINUM PRODUCTS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310825311.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-06
Publication Date
2025-04-29
Estimated Expiration
2043-07-06

AI Technical Summary

Technical Problem

The existing aluminum alloy frames have problems such as poor corrosion resistance and insufficient cleaning in the application of new energy vehicles, which are difficult to meet the needs of modern new energy vehicles.

Method used

A powder spraying process for aluminum alloy frames for new energy vehicles is adopted, including pretreatment and spraying process for aluminum alloy frames. The pretreatment steps include grinding, water washing, industrial acid removal, mixed acid activation, etc. The spraying process uses powder coating made of raw materials such as polyester resin, epoxy resin, anticorrosion fillers and additives, and sprays evenly through a spray gun and cures in the baking room.

Benefits of technology

It realizes the excellent corrosion resistance and easy cleaning performance of aluminum alloy frames, meeting the high requirements of new energy vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004324992730000091
    Figure BDA0004324992730000091
Patent Text Reader

Abstract

The invention discloses a powder spraying process for an aluminum alloy frame for a new energy vehicle, belongs to the technical field of aluminum alloy profiles, and comprises the following steps: preparing the following raw materials in parts by weight: 220-240 parts of polyester resin, 30-40 parts of glycerol epoxy resin, 40-50 parts of anticorrosive filler, 15-20 parts of auxiliary agent, 10-13 parts of curing agent, and 3-5 parts of leveling agent; adding the above raw materials into a mixer according to proportion and mixing, and extruding through a twin-screw extruder to obtain a powder coating; hanging a pretreated aluminum alloy frame in a powder spraying room, spraying the powder coating evenly onto the surface of the pretreated aluminum alloy frame through a spray gun, and baking to obtain the aluminum alloy frame for the new energy vehicle; the invention first pretreats the aluminum alloy frame profile, sprays the powder coating made of raw materials such as polyester resin, epoxy resin, anticorrosive filler and auxiliary agent, and obtains an aluminum alloy frame for a new energy vehicle with excellent corrosion resistance and easy-to-clean performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum alloy profiles, and specifically relates to a powder spraying process for an aluminum alloy frame for a new energy vehicle. Background Art

[0002] With the development of automobile industrialization, new energy vehicles are becoming more and more popular. In order to meet the need for lightweight automobile bodies, aluminum alloys are widely used as new energy vehicle body frame materials based on their good mechanical properties and low density characteristics. With the development of the market, people have put forward higher requirements for aluminum alloy frames for new energy vehicles, one is corrosion resistance, and the other is easy cleaning.

[0003] Since aluminum alloy materials themselves have poor corrosion resistance, they often need to be surface treated to enhance their corrosion resistance. For example, Chinese patent CN110280466B announces an electrostatic spraying process for aluminum alloy profiles, and Chinese patent CN105132900B announces an environmentally friendly titanium-zirconium conversion treatment / electrostatic spraying anti-corrosion treatment process for aluminum alloy surfaces. Both of them pre-treat the aluminum alloy material and then electrostatically spray powder coating, which both achieve a certain degree of enhanced anti-corrosion effect, but do not improve the easy-to-clean characteristics of the aluminum alloy material, making it difficult to meet the needs of aluminum alloy frame materials for modern new energy vehicles. Therefore, it is necessary to provide a new spraying process for aluminum alloy frames for new energy vehicles to improve the corrosion resistance of the aluminum alloy frame while providing its easy-to-clean performance. Summary of the invention

[0004] The purpose of the present invention is to provide a powder spraying process for an aluminum alloy frame for a new energy vehicle to solve the problems in the background technology.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A powder spraying process for an aluminum alloy frame for a new energy vehicle comprises the following steps:

[0007] S1, grinding and washing the aluminum alloy frame, degreasing with industrial acid, washing with water for the second time, activating with mixed acid, washing with water and drying, to obtain a pretreated aluminum alloy frame;

[0008] S2. Hang the pretreated aluminum alloy frame in a powder spraying room, and evenly spray the powder coating onto the surface of the pretreated aluminum alloy frame through a spray gun, control the distance between the spray gun and the pretreated aluminum alloy frame to be 180-260 mm, the voltage to be 50-70 kV, the current to be 50-60 μA, the compressed air pressure to be 0.5 MPa, and stand for 2-3 minutes, then transfer to a baking room at a temperature of 180-220° C. for treatment for 10-16 minutes to melt, level and solidify the powder coating, and cool to room temperature to obtain the aluminum alloy frame for new energy vehicles.

[0009] As a further embodiment of the present invention, the powder coating is prepared by the following steps:

[0010] Prepare the following raw materials in parts by weight: 220-240 parts of polyester resin, 30-40 parts of glycerol epoxy resin, 40-50 parts of anticorrosive filler, 15-20 parts of additives, 10-13 parts of curing agent, and 3-5 parts of leveling agent; add the above raw materials into a mixer according to proportion and mix for 10-20 minutes, then pass through a twin-screw extruder, melt extrude at 90-100°C, cool, and crush to a particle size of 10-30 microns.

[0011] As a further embodiment of the present invention, the auxiliary agent is prepared by the following steps:

[0012] Toluene diisocyanate and DMF are added to a flask, and the temperature is raised to 80°C under nitrogen protection. A DMF solution of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is added under stirring, and the reaction is carried out for 2-3 hours. The temperature is then cooled to room temperature, and dibutyltin dilaurate is added dropwise. After the addition is completed, a DMF solution of 2,2,3,3,4,4,5,5-octafluoro-1-pentanol is added, and the reaction is stirred at 80-90°C for 2-3 hours. After the reaction is completed, DMF is removed by reduced pressure distillation to obtain an auxiliary agent, toluene diisocyanate, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, dibutyltin dilaurate and 2,2,3 The dosage ratio of 3,4,4,5,5-octafluoro-1-pentanol is 4-4.2g:2.8g:0.11-0.15g:6-6.2g. First, the terminal amino group of 1,3-bis(3-aminopropyl)-1,1,3,3,-tetramethyldisiloxane is reacted with the isocyanate group of toluene diisocyanate to form an intermediate product containing a urea group. By controlling the dosage of the raw materials, the intermediate product molecule still contains an isocyanate group. Then, the isocyanate group is reacted with the hydroxyl group of 2,2,3,3,4,4,5,5-octafluoro-1-pentanol to introduce a fluorocarbon chain into the structure of the intermediate product to obtain an auxiliary agent. It can be seen that the auxiliary agent contains a silicon-oxygen-silicon structure, a urea group and a fluorocarbon chain.

[0013] As a further embodiment of the present invention, the anticorrosive filler is prepared by the following steps:

[0014] The invention discloses a method for preparing a preservative filler comprising adding tris(hydroxymethyl)aminomethane to deionized water, adjusting the pH value to 8.5 with a 1 mol / L hydrochloric acid solution, stirring for 30 minutes, ultrasonically treating for 30 minutes, adding filler particles and anhydrous ethanol, continuing ultrasonication for 1 hour, finally adding dopamine hydrochloride, ultrasonically treating for 2 hours, stirring and reacting at 20°C for 2-4 hours, and after the reaction is completed, centrifuging at a speed of 4000 rpm for 10 minutes, washing the precipitate with deionized water until the washing liquid is neutral, freeze-drying for 12 hours, and grinding to obtain the preservative filler; the amount ratio of tris(hydroxymethyl)aminomethane, deionized water, filler particles, anhydrous ethanol and dopamine hydrochloride is 1:2. .11g:1000-1500mL:10g:300-500mL:4g, the filler particles are nano-silicon dioxide, multi-walled carbon nanotubes, and molybdenum disulfide nanosheets in a mass ratio of 5-10:2-3:3-5, wherein the nano-silicon dioxide is spherical, the multi-walled carbon nanotubes are tubular, and the molybdenum disulfide is flaky. The above three materials are used as fillers, and after being modified with dopamine, the hydrophilicity of the surface of the filler ions is reduced, and they are added to the powder coating. Through the combination of filler particles of different dimensions, a dense three-dimensional shielding network is formed, which improves the rigidity of the coating while hindering the invasion of corrosive media.

[0015] As a further embodiment of the present invention, the curing agent is triglycidyl isocyanurate, and the leveling agent is composed of polyacrylate and propylene glycol alginate in a mass ratio of 4:13.

[0016] Beneficial effects of the present invention:

[0017] 1. The present invention first pre-treats the aluminum alloy frame profile, including water-based and pickling steps, and then performs a spraying process to spray a powder coating made of raw materials such as polyester resin, epoxy resin, anti-corrosion fillers and additives, so as to obtain an aluminum alloy frame for new energy vehicles with excellent corrosion resistance and easy cleaning performance.

[0018] 2. The present invention adds a self-made auxiliary agent to the powder coating, and the auxiliary agent contains a silicon-oxygen-silicon structure, a urea group and a fluorocarbon chain structure. The introduction of the silicon-oxygen-silicon structure can improve the heat resistance and hydrophobicity of the powder coating. The migration of the fluorocarbon chain can form a hydrophobic layer on the surface of the coating, further improving the self-cleaning properties of the coating. The urea group can react with the epoxy group in the epoxy resin to "anchor" the auxiliary agent in the coating through chemical bonds, giving the coating stable self-cleaning properties.

[0019] 3. The present invention adds self-made anti-corrosion fillers to the powder coating, specifically a mixture of dopamine-treated nano-silicon dioxide, multi-walled carbon nanotubes, and molybdenum disulfide nanosheets, wherein the nano-silicon dioxide is spherical, the multi-walled carbon nanotubes are tubular, and the molybdenum disulfide is flaky. The above three materials are used as fillers, which are modified by dopamine to reduce the hydrophilicity of the surface of the filler ions. They are added to the powder coating, and a dense three-dimensional shielding network is formed through the combination of filler particles of different dimensions. While improving the rigidity of the coating, it hinders the invasion of corrosive media and improves the corrosion resistance of the coating. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Example 1

[0022] An auxiliary agent is prepared by the following steps:

[0023] 4 g of toluene diisocyanate and 20 mL of DMF were added to a flask. Under nitrogen protection, the temperature was raised to 80°C. A solution consisting of 2.8 g of 1,3-bis(3-aminopropyl)-1,1,3,3,-tetramethyldisiloxane and 20 mL of DMF was added under stirring. The reaction was continued for 2 h. The temperature was then cooled to room temperature. 0.11 g of dibutyltin dilaurate was added dropwise. After the addition was completed, a solution consisting of 6 g of 2,2,3,3,4,4,5,5-octafluoro-1-pentanol and 50 mL of DMF was added. The reaction was stirred at 80°C for 2 h. After the reaction was completed, DMF was removed by reduced pressure distillation to obtain an auxiliary agent.

[0024] Example 2

[0025] An auxiliary agent is prepared by the following steps:

[0026] 4.2 g of toluene diisocyanate and 20 mL of DMF were added to a flask. Under nitrogen protection, the temperature was raised to 80°C. A solution consisting of 2.8 g of 1,3-bis(3-aminopropyl)-1,1,3,3,-tetramethyldisiloxane and 20 mL of DMF was added under stirring. The reaction was continued for 3 h. The temperature was then cooled to room temperature. 0.15 g of dibutyltin dilaurate was added dropwise. After the addition was completed, a solution consisting of 6.2 g of 2,2,3,3,4,4,5,5-octafluoro-1-pentanol and 50 mL of DMF was added. The reaction was stirred at 90°C for 3 h. After the reaction was completed, DMF was removed by reduced pressure distillation to obtain an auxiliary agent.

[0027] Example 3

[0028] An anti-corrosion filler is prepared by the following steps:

[0029] 12.11 g of tris(hydroxymethyl)aminomethane) was added to 1000 mL of deionized water, and the pH was adjusted to 8.5 with a 1 mol / L hydrochloric acid solution. After stirring for 30 min, the mixture was ultrasonically treated for 30 min. 10 g of filler particles and 300 mL of anhydrous ethanol were added, and the ultrasonic treatment was continued for 1 h. Finally, 4 g of dopamine hydrochloride was added, and the mixture was ultrasonically treated for 2 h. The mixture was stirred and reacted at 20°C for 2 h. After the reaction was completed, the mixture was centrifuged at 4000 rpm for 10 min. The precipitate was washed with deionized water until the washing liquid was neutral, and the mixture was freeze-dried for 12 h. The mixture was ground to obtain an anticorrosive filler. The filler particles were composed of nano-silica, multi-walled carbon nanotubes, and molybdenum disulfide nanosheets in a mass ratio of 5:2:3.

[0030] Example 4

[0031] An anti-corrosion filler is prepared by the following steps:

[0032] 12.11 g of tris(hydroxymethyl)aminomethane) was added to 1500 mL of deionized water, and the pH was adjusted to 8.5 with a 1 mol / L hydrochloric acid solution. After stirring for 30 min, the mixture was ultrasonically treated for 30 min. 10 g of filler particles and 500 mL of anhydrous ethanol were added, and the ultrasonic treatment was continued for 1 h. Finally, 4 g of dopamine hydrochloride was added, and the mixture was ultrasonically treated for 2 h. The mixture was stirred and reacted at 20°C for 4 h. After the reaction was completed, the mixture was centrifuged at 4000 rpm for 10 min. The precipitate was washed with deionized water until the washing liquid was neutral, and the mixture was freeze-dried for 12 h. The mixture was ground to obtain an anticorrosive filler. The filler particles were composed of nano-silica, multi-walled carbon nanotubes, and molybdenum disulfide nanosheets in a mass ratio of 10:3:5.

[0033] Example 5

[0034] A powder spraying process for an aluminum alloy frame for a new energy vehicle comprises the following steps:

[0035] S1. The aluminum alloy frame is first polished with 400# water sandpaper, then polished with 800# water sandpaper, sprayed with water, the spray temperature is 55°C, the spray pressure is 0.1MPa, the spray time is 1min, blown dry, immersed in process acid for 2min for degreasing, sprayed with water, immersed in mixed acid for 3min for activation treatment, sprayed with water, and dried. The composition of the industrial acid is 80g / LH2SO4, 25g / LH3PO4, 10g / L HF, 0.5g / L OP-10 emulsifier, and the solvent is water; the composition of the mixed acid is 15g / LHNO3, 20g / L H3PO4, 25g / L H2SO4, and the solvent is water, to obtain a pretreated aluminum alloy frame;

[0036] S2. Hang the pretreated aluminum alloy frame in the powder spraying room, and evenly spray the powder coating onto the surface of the pretreated aluminum alloy frame through a spray gun, control the distance between the spray gun and the pretreated aluminum alloy frame to be 180 mm, the voltage to be 50 kV, the current to be 50 μA, the compressed air pressure to be 0.5 MPa, and stand for 2 minutes. Then transfer it to a baking room at a temperature of 180°C for 10 minutes to melt, level and solidify the powder coating, and cool it to room temperature to obtain the aluminum alloy frame for new energy vehicles.

[0037] The powder coating is prepared by the following steps:

[0038] Prepare the following raw materials in parts by weight: 220 parts of polyester resin, 30 parts of glycerol epoxy resin, 40 parts of the anticorrosive filler of Example 3, 15 parts of the auxiliary agent of Example 1, 10 parts of curing agent, and 3 parts of leveling agent; add the above raw materials in proportion to a mixer and mix for 10 minutes, then pass through a twin-screw extruder, melt-extrude at 90-100°C, cool, and crush to a particle size of 10-30 microns.

[0039] Among them, polyester resin was purchased from Guangzhou Nashun Chemical Technology Co., Ltd., with the item number: 191A; glycerol epoxy resin can be purchased from Wuxi Qianguang Chemical Raw Materials Co., Ltd., with the brand number: B-63 (662#); the curing agent is triglycidyl isocyanurate, and the leveling agent is composed of polyacrylate and propylene glycol alginate in a mass ratio of 4:13. Polyacrylate can be purchased from Changzhou Enke New Material Technology Co., Ltd., with the model number: NEO-3058; propylene glycol alginate can be purchased from Henan Guanqi Biotechnology Co., Ltd., with the item number: u8522.

[0040] Example 6

[0041] A powder spraying process for an aluminum alloy frame for a new energy vehicle comprises the following steps:

[0042] S1, polishing and washing the aluminum alloy frame, degreasing with industrial acid, washing with water for the second time, activating with mixed acid, washing with water and drying to obtain a pretreated aluminum alloy frame; the specific steps are the same as step S1 in Example 5;

[0043] S2. Hang the pretreated aluminum alloy frame in the powder spraying room, and evenly spray the powder coating onto the surface of the pretreated aluminum alloy frame through a spray gun, control the distance between the spray gun and the pretreated aluminum alloy frame to be 220 mm, the voltage to be 60 kV, the current to be 55 μA, the compressed air pressure to be 0.5 MPa, and stand for 2.5 minutes. Then transfer it to a baking room at a temperature of 200°C for 14 minutes to melt, level and solidify the powder coating, and cool it to room temperature to obtain the aluminum alloy frame for new energy vehicles.

[0044] The powder coating is prepared by the following steps:

[0045] Prepare the following raw materials in parts by weight: 230 parts of polyester resin, 35 parts of glycerol epoxy resin, 45 parts of the anticorrosive filler of Example 3, 18 parts of the auxiliary agent of Example 2, 12 parts of curing agent, and 4 parts of leveling agent; add the above raw materials in proportion to a mixer and mix for 15 minutes, then pass through a twin-screw extruder, melt-extrude at 90-100°C, cool, and crush to a particle size of 10-30 microns.

[0046] Among them, polyester resin was purchased from Guangzhou Nashun Chemical Technology Co., Ltd., with the item number: 191A; glycerol epoxy resin can be purchased from Wuxi Qianguang Chemical Raw Materials Co., Ltd., with the brand number: B-63 (662#); the curing agent is triglycidyl isocyanurate, and the leveling agent is composed of polyacrylate and propylene glycol alginate in a mass ratio of 4:13. Polyacrylate can be purchased from Changzhou Enke New Material Technology Co., Ltd., with the model number: NEO-3058; propylene glycol alginate can be purchased from Henan Guanqi Biotechnology Co., Ltd., with the item number: u8522.

[0047] Example 7

[0048] A powder spraying process for an aluminum alloy frame for a new energy vehicle comprises the following steps:

[0049] S1, polishing and washing the aluminum alloy frame, degreasing with industrial acid, washing with water for the second time, activating with mixed acid, washing with water and drying to obtain a pretreated aluminum alloy frame; the specific steps are the same as step S1 in Example 5;

[0050] S2. Hang the pretreated aluminum alloy frame in the powder spraying room, and evenly spray the powder coating onto the surface of the pretreated aluminum alloy frame through a spray gun, control the distance between the spray gun and the pretreated aluminum alloy frame to be 260 mm, the voltage to be 70 kV, the current to be 60 μA, the compressed air pressure to be 0.5 MPa, and stand for 3 minutes. Then transfer it to a baking room at a temperature of 220°C for 16 minutes to melt, level and solidify the powder coating, and cool it to room temperature to obtain the aluminum alloy frame for new energy vehicles.

[0051] The powder coating is prepared by the following steps:

[0052] Prepare the following raw materials in parts by weight: 240 parts of polyester resin, 40 parts of glycerol epoxy resin, 50 parts of the anticorrosive filler of Example 4, 20 parts of the auxiliary agent of Example 2, 13 parts of curing agent, and 5 parts of leveling agent; add the above raw materials in proportion to a mixer and mix for 20 minutes, then pass through a twin-screw extruder, melt-extrude at 90-100°C, cool, and crush to a particle size of 10-30 microns.

[0053] Among them, polyester resin was purchased from Guangzhou Nashun Chemical Technology Co., Ltd., with the item number: 191A; glycerol epoxy resin can be purchased from Wuxi Qianguang Chemical Raw Materials Co., Ltd., with the brand number: B-63 (662#); the curing agent is triglycidyl isocyanurate, and the leveling agent is composed of polyacrylate and propylene glycol alginate in a mass ratio of 4:13. Polyacrylate can be purchased from Changzhou Enke New Material Technology Co., Ltd., with the model number: NEO-3058; propylene glycol alginate can be purchased from Henan Guanqi Biotechnology Co., Ltd., with the item number: u8522.

[0054] Comparative Example 1

[0055] Compared with Example 5, the anti-corrosion filler in the powder coating of Example 5 is replaced by a mixture of nano-silicon dioxide, multi-walled carbon nanotubes, and molybdenum disulfide nanosheets in a mass ratio of 5:2:3, and the remaining raw materials and processing steps are the same as Example 5.

[0056] Comparative Example 2

[0057] Compared with Example 5, the additives in the powder coating of Example 5 are removed, and the remaining raw materials and processing steps are the same as Example 5.

[0058] The performance tests were conducted on the aluminum alloy frames for new energy vehicles obtained in Examples 5 to 7 and Comparative Examples 1 to 2. The test contents are as follows:

[0059] Acid salt spray corrosion resistance: Draw two cross lines on the sample along the diagonal line, which are deep to the substrate. The line segments do not pass through the diagonal of the sample and each end point is equidistant from the corresponding diagonal. Then, perform the acetic acid salt spray test according to GB / T10125-2012 "Artificial atmosphere corrosion test salt spray test". After 1000 hours, visually inspect the coating surface and the degree of unilateral penetration under the film.

[0060] Self-cleaning performance: refer to the test method for stain resistance of exterior wall coatings in the national standard GB / T9780-2013 "Test method for stain resistance of building coatings"; specifically, the fly ash is stirred evenly at a water-ash mass ratio of 0.9:1 to form a suspension for standby use; the initial reflection coefficient of the coating is measured at the upper, middle and lower positions in the coating of the sample to be tested, and the average value A is taken respectively, and the suspension is evenly brushed on the coating surface first horizontally and then vertically with a wolf hair brush, and the brushing amount of the pollution source suspension is (0.7±0.1)g; under standard test conditions, it is placed for two hours; it is placed in a flushing device for flushing and placed for 24 hours. After 5 cycles, the reflection coefficient is measured at the upper, middle and lower positions of the coating, and the average value is taken, recorded as B. The stain resistance of the coating is calculated according to the following formula: X=(AB) / A×100;

[0061] The test results are shown in Table 1:

[0062] Table 1

[0063]

[0064] It can be seen from Table 1 that the aluminum alloy frame prepared by the present invention not only has good corrosion resistance, but also has high anti-fouling performance, and has good anti-corrosion performance and aesthetic effect when used in new energy vehicles.

[0065] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0066] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A powder spraying process for aluminum alloy frame for new energy vehicles, characterized in that: The following steps are involved: The first step is to prepare the following raw materials by weight: 220-240 parts of polyester resin, 30-40 parts of glycerol epoxy resin, 40-50 parts of anticorrosive filler, 15-20 parts of additives, 10-13 parts of curing agent, and 3-5 parts of leveling agent; add the above raw materials into a mixer according to proportion and mix for 10-20 minutes, pass through a twin-screw extruder, extrude, cool, and crush to obtain a powder coating; The second step is to hang the pretreated aluminum alloy frame in a powder spraying room, spray the powder coating evenly onto the surface of the pretreated aluminum alloy frame by a spray gun, and bake it in a room at 180-220° C. for 10-16 minutes to obtain the aluminum alloy frame for new energy vehicles; The additive is prepared by the following steps: Toluene diisocyanate and DMF are added to a flask, and the temperature is raised to 80°C under nitrogen protection. A DMF solution of 1,3-bis(3-aminopropyl)-1,1,3,3,-tetramethyldisiloxane is added under stirring, and the reaction is carried out for 2-3 hours. The temperature is then cooled to room temperature, and dibutyltin dilaurate is added dropwise. After the addition is completed, a DMF solution of 2,2,3,3,4,4,5,5-octafluoro-1-pentanol is added, and the reaction is stirred at 80-90°C for 2-3 hours. After the reaction is completed, DMF is removed by vacuum distillation to obtain an auxiliary agent; The usage ratio of toluene diisocyanate, 1,3-bis(3-aminopropyl)-1,1,3,3,-tetramethyldisiloxane, dibutyltin dilaurate and 2,2,3,3,4,4,5,5-octafluoro-1-pentanol is 4-4.2g:2.8g:0.11-0.15g:6-6.2g; The anti-corrosion filler is a mixture of dopamine-treated nano-silicon dioxide, multi-walled carbon nanotubes, and molybdenum disulfide nanosheets.

2. A powder spraying process for aluminum alloy frame for new energy vehicles according to claim 1, characterized in that: The pretreated aluminum alloy frame is obtained by sequentially grinding and washing the aluminum alloy frame, degreasing with industrial acid, washing with a second time, activating with mixed acid, and washing and drying.

3. A powder spraying process for aluminum alloy frame for new energy vehicles according to claim 1, characterized in that: During the powder spraying process, the distance between the spray gun and the pretreated aluminum alloy frame is controlled to be 180-260 mm, the voltage is 50-70 kV, the current is 50-60 μA, and the compressed air pressure is 0.5 MPa.

4. A powder spraying process for aluminum alloy frame for new energy vehicles according to claim 1, characterized in that: The anti-corrosion filler is made by the following steps: Add tris(hydroxymethyl)aminomethane) into deionized water, adjust the pH value to 8.5 with hydrochloric acid solution, stir for 30 minutes and then ultrasonically treat for 30 minutes, add filler particles and anhydrous ethanol, continue ultrasonication for 1 hour, finally add dopamine hydrochloride, ultrasonically treat for 2 hours, stir and react at 20°C for 2-4 hours, after the reaction is completed, centrifuge at 4000 rpm for 10 minutes, wash the precipitate with deionized water until the washing liquid is neutral, freeze-dry for 12 hours, grind to obtain an antiseptic filler.

5. A powder spraying process for aluminum alloy frame for new energy vehicles according to claim 4, characterized in that: The dosage ratio of tris(hydroxymethyl)aminomethane, deionized water, filler particles, anhydrous ethanol and dopamine hydrochloride is 12.11 g: 1000-1500 mL: 10 g: 300-500 mL: 4 g.

6. A powder spraying process for aluminum alloy frame for new energy vehicles according to claim 4, characterized in that: The filler particles are composed of nano silicon dioxide, multi-walled carbon nanotubes and molybdenum disulfide nanosheets in a mass ratio of 5-10:2-3:3-5.

7. A powder spraying process for aluminum alloy frame for new energy vehicles according to claim 1, characterized in that: The curing agent is triglycidyl isocyanurate, and the leveling agent is composed of polyacrylate and propylene glycol alginate in a mass ratio of 4:13.

Citation Information

Patent Citations

  • Environmentally friendly titanium-zirconium conversion treatment / electrostatic spraying anti-corrosion treatment process for aluminum alloy surfaces

    CN105132900B

  • An electrostatic spraying process for aluminum alloy profiles

    CN110280466B

  • Novel abrasion-resistant, anti-corrosion and anti-static coating and preparation method thereof

    CN105219219A

  • Electrostatic spraying process for aluminum alloy profiles

    CN110280466A

  • Preparation method of polydopamine modified molybdenum disulfide composite epoxy powder coating

    CN113637383A